Implementasi Permainan Ular Tangga Dalam Mengembangkan Motorik Kasar Pada Anak Usia 5-6 Tahun Di PAUD Nurul Ihsan - Saniati Saniati; Muthia Sari; Devi Ayu Kurniawati; Novita Sari; Nuryati Nuryati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Gross motor development is an important aspect of early childhood education because it plays a role in supporting children's physical, cognitive, social, and emotional readiness. However, in practice, gross motor stimulation in PAUD institutions is still not optimal and tends to be dominated by passive activities. This study aims to describe the implementation of the snakes and ladders floor game in developing gross motor skills of children aged 5–6 years at PAUD Nurul Ihsan. This study used a qualitative method with a descriptive approach. The subjects were 13 children in group B consisting of 5 boys and 8 girls, and two class teachers as key informants. Data collection techniques included observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the snakes and ladders floor game was able to improve children's gross motor skills, especially in aspects of balance, motor coordination, large muscle strength, agility, body control, courage to move, and physical endurance. Children also showed increased self-confidence and social skills, such as waiting their turn and following the rules of the game. It can be concluded that the snakes and ladders floor game is an effective, fun learning medium, and in accordance with the principles of learning through play in PAUD. This game has the potential to be a holistic learning approach in optimizing the gross motor development of early childhood.